Correlation analysis of daily water levels in rivers of the Kaliningrad region based on observation results in 2008–2021 - V. A. Naumov; N. R. Ahmedova (Vestnik MGSU)
Introduction. When justifying design decisions in hydraulic engineering, developing measures for the use and protection of water resources, information on the intra-annual distribution of runoff is of practical and scientific interest. The paper presents the results of a correlation analysis of daily water levels in the rivers of the Kaliningrad region, based on the results of observations in years with different water content from 2008 to 2021.Materials and methods. The statistical analysis of the data set of observations of daily water levels in 12 river stations of the Kaliningrad region for the period from 2008 to 2021 was carried out. The data source was the automated information system of state monitoring of water bodies. The observation results were processed in Mathcad environment.Results. Pair correlation coefficients between daily water levels in the studied river stations of the Kaliningrad region were calculated. The average, maximum and minimum pair correlation coefficients of daily water levels in the considered stations were determined. The dependence of pair correlation coefficients of daily water levels in two stations located in the same river system (The Angrapa River – Berestovo gauging station – The Pregolya River – Gvardeysk gauging station) and for different river systems (The Mamonovka River – Mamonovo gauging station – The Pregolya River – Chernyakhovsk gauging station) was determined.Conclusions. It was found that the closest stochastic relationship of daily water levels is observed near the Neman and Matrosovka Rivers; in dry years, the values of the pair correlation coefficients of daily water levels decrease in the studied stations; The Pregolya river (Gvardeysk gauging station) and the Instruch River (Ulyanovo gauging station) should be recommended as analogues for watercourses of the Kaliningrad region. The obtained results can be used for the development of measures for the use and protection of water resources in the region.